Reaction engineering during biomass gasification and conversion to energy. (1st March 2023) - Verma, Shivpal; Dregulo, Andrei Mikhailovich; Kumar, Vinay; Bhargava, Preeti Chaturvedi; Khan, Nawaz; Singh, Anuradha; Sun, Xinwei; Sindhu, Raveendran; Binod, Parameswaran; Zhang, Zengqiang; Pandey, Ashok; Awasthi, Mukesh Kumar
Abstract: Bioenergy, as a perspective of the global energy paradigm, makes a significant contribution to the increase in global energy demand and the development of technologies for converting biomass into energy. Biomass gasification is the most preferred option for thermochemical processing. We conducted a comprehensive analysis of biomass gasification and concluded: 1) that the properties of biomass can be both attractive from the point of view of obtaining value-added products and limiters in the final use of biomass products; and 2) most publications are focused on a narrow range of issues dedicated to a specific technology. To eliminate these shortcomings, we consider as common factors affecting the efficiency of thermochemical processes: type of biomass and humidity; gasification agents range of operating temperatures of gasifiers; efficiency of heat transfer; pressure and actually obtaining the necessary characteristics of the final products obtained in combinations of various thermochemical methods of processing biomass, and particular factors: the influence of new techniques (chemical cyclic gasification and catalysis), design features of gasifiers and variability of their use. Based on the conducted research, we believe that the hybrid approach (combining thermochemical, hydrothermal and biological methods) could help in solving the above-mentioned problems and can contribute to the circular economy by reducing waste production and obtaining value-added by-products through the use of machine learning and artificial intelligence methods. Graphical abstract: Image 1 Highlights: Gasification of biomass and organic waste for energy production is reviewed. Biomass gasification makes it possible to obtain products with high added value is discussed. Biomass gasification is a complex and high-cost production. Constant optimization by co-variating physico-chemical processes is investigate.